Outcome of Spine Fixation for Unstable Fractures at Dorsolumbar Junction including Fractured Vertebrae in Pedicular Screw Fixation - Muhammad Bilal Khan, Ibrar Ali, Abdul Qadir Khan, Ahsan Ul Haq, Abdul Waheed, Abdus Saboor Awan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The most serious injury that may change a person's life is a spinal cord injury that results in loss of neurological function. Many people in Pakistan suffer from spinal injuries every year. Although research on spinal injuries has been published in Pakistan, it is still unclear how often spinal injuries are there. Objective: To assess the radiological and clinical outcomes of transpedicular screw fixation for fractures of the spine, including vertebral fractures Methodology: This prospective research carried out by the Department of Orthopaedics and Spine Surgery, PIMS, Islamabad and Health Net Hospital Phase 5, Hayatabad Peshawar between November 2022 and April, 2023. This research comprised 130 individuals with single-level fractures ranging from D11 to L2. In every patient, a dorso-lumbar MRI and a full spine X-ray were performed. Clinical criteria included back pain measured by the Visual Analogue Score (VAS) and disability measured by the Oswestry Disability Index (ODI). Version 23 of the SPSS software was used to analyze the data. Results: A total of 130 patients were included in this study. The mean age (SD) of the enrolled patients was 32.8 (±2.11) years. There were 97 (74.62%) males patients while the female patients were 33 (25.38%). A statistical significant improvement was observed post-operatively in posterior vertebral height, anterior vertebral height, Cobb angle and sagittal index. (p<0.05). Statistical significant improvement in Oswestry disability index (ODI) and reduction in VAS was observed in our study. (p<0.05). The post-operative complications were observed in only 12 (9.24%) Patients. Conclusion: Excellent radiological and clinical results were obtained in our investigation using transpedicular screw fixation that included the fractured vertebrae. By providing an additional pedicle for fixation, it shortened the fixation segment and enhanced biomechanical stability while also aiding in reduction and repair of deformities. Therefore, in the case of dorso-lumbar spine fractures, we highly advise transpedicular screw stabilization of the fractured vertebra. Keywords: Spine fixation; Unstable fractures; Dorsolumbar junction.